Association of follicle-to-oocyte index and clinical pregnancy in IVF treatment: A retrospective study of 4,323 fresh embryo transfer cycles - Li, Peiyi; Chen, Zhiyun (Frontiers in Endocrinology, 2022)
Objective The aim of this study is to investigate whether the follicle-to-oocyte index [FOI: (number of retrieved oocytes/antral follicle count) × 100] was associated with clinical pregnancy after fresh cleavage transfer. Design The framework used to organize this study is retrospective cohort analysis. Setting The study was performed in a single in vitro fertilization center in a public hospital. Patients In total, 4,323 fresh embryo transfer cycles from 1 August 2011 to 31 January 2022 were retrospectively analyzed. Data were designated into three groups according to FOI tertile values. Interventions There are no interventions in this study. Main outcome measure The primary outcome measure is the clinical pregnancy rate (CPR). Results A total of 4,323 patients were included in the study. According to their FOI, patients were divided into low (FOI ≤ 0.70, n = 1,434), medium (FOI = 0.71–0.95, n = 1,070), and high (FOI = 0.96–1.00, n = 1,819) tertile groups. A significant statistical increase in the CPR from the lowest to the highest tertile FOI group was detected (47.28%, 51.78%, and 51.57%; P =0.026). After adjusted for potential confounders, multivariate logistic regression analysis revealed a positive association between FOI and CPR [odds ratio (OR) = 1.57; 95% confidence interval (CI): 1.18–2.11]. Each standard deviation increments in FOI (SD = 0.24) corresponded to a 20% increase in the CPR. Trend analysis also showed that FOI tertile groups were positively associated with CPR (P for trend = 0.010). Smooth curve fitting indicated the existence of a linear relationship across the entire range of FOI. No optimal cutoff value of FOI for prognosing CPR was found in smooth curve fitting analysis. Moreover, subgroup analyses suggested that the association was significantly stronger in the single cleavage transfer cycle (OR = 2.04; 95% CI: 1.14–3.65). Conclusions FOI is an independent variable in prediction for CPR in fresh embryo transfer cycle, especially in the single cleavage transfer cycle.